FIP200 controls the TBK1 activation threshold at SQSTM1/p62-positive condensates - David Schlütermann (Nature Portfolio, 2021)
Abstract The protein kinase TBK1 is a central regulator of innate immune responses and autophagy, and ablation of either function has been linked to neuroinflammatory or degenerative diseases. Autophagy is an intracellular process that recycles old or damaged proteins and organelles. In recent years, the TBK1-dependent regulation of autophagy pathways has been characterized. However, the autophagy-dependent regulation of TBK1 activity awaits further clarification. Here, we observed that TBK1 is recruited to SQSTM1/p62-containing aggregates via the selective autophagy receptor TAX1BP1. In these aggregates, TBK1 phosphorylates SQSTM1/p62 at serine 403 and thus presumably regulates the efficient engulfment and clearance of these structures. We found that TBK1 activation is strongly increased if FIP200, a component of the autophagy-inducing ULK1 complex, is not present or cannot bind to TAX1BP1. Given our collective findings, we hypothesize that FIP200 ensures the inducible activation of TBK1 at SQSTM1/p62 condensates.